Agreement and Interference in Direct Object Clitic Production in Italian Monolingual Children - Arosio, Fabrizio; Giustolisi, Beatrice (Frontiers in Communication, 2019)
Italian speaking children optionally omit third singular direct object clitics (3DO) until at least age four years. In a set of two studies, we investigated whether omissions and errors depend on intervention phenomena. We discussed a model of syntactic intervention in which the subject of a sentence intervenes when the clitic moves from its initial merging position to a higher position above the subject. We argued that omissions and errors arise when retrieving from memory the clitic to achieve an agreement operation in a context of syntactic intervention. We argued that working memory limitations impact on the clitic retrieving operation cued by lexical and representational features. In Study 1, we elicited the production of 3DO clitics in sentences with a full lexical subject. The 3rd singular subject and the 3DO clitic were matched or not in gender. Results of Study 1 showed that when there is a gender mismatch between the subject and the clitic children with limited memory resources optionally make clitic gender errors or even replace the 3DO clitic with a postverbal full DP. We explained these results in an intervention model in which the external verb lexical argument (the lexical subject) is erroneously retrieved for achieving the agreement operation involving the movement of the clitic to its surface position. In Study 2 we investigated whether the problems found in Study 1 depend on phonological priming or structural intervention. We elicited the production of 3DO clitics in sentences with a null subject. in conditions of gender matching and mismatching. Results showed that in sentences with a gender mismatch children with limited memory resourches tend to produce a clitic with the incorrect gender or to optionally replace it with a full lexical postverbal DP. This suggests that a null subject intervenes in the same way a lexical subject does. Overall results indicate that the interference errors are not dependent on phonological attraction but have a structural nature and are modulated by short-term memory resources.